Evaluation of Front Line Demonstration on chickpea in Dewas District - Bhargav , K S; Pandey, Ankita; Sharma , R P; Singh, Awdesh; Kumar, Manish (Indian Journal of Extension Education, 2015)
Chickpea (Cicer arietinum L.) is the premier pulse, which fixes atmospheric nitrogen through symbiotic action. Low  productivity of traditional varieties of gram is a cause of concern for farmers' at large. To overcome the problem of low  yield, Krishi Vigyan Kendra, Dewas has conducted front line demonstrations in the different localities of Dewas district.  Cultivation of high yielding varieties of gram viz. JG-412, JG-130, JG-11 and JG-16 had given yield increases of 25.9,  16.2, 20.7 and 25 per cent respectively over local check. The highest extension gap 302 kg/ha was recorded during the year  2012-13 (JG-16), The technology index was lowest for the variety JG-130 (14.30%), indicated that variety JG-130 has  performed better in Malwa platue and may accelerate the adoption of short duration variety to increase the productivity of  gram in this area.
Keywords: Front line demonstration; technology gap; extension gap; technology index; chickpea